1977
DOI: 10.1007/bf01223273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-term glucagon infusion on kidney function in normal man

Abstract: Summary. Kidney function was studied in six normal males before and during a 2 h glucagon (10ng/kg/min) infusion. The following variables were determined during each 20 min clearance period; glomerular filtration rate (GFR), renal plasma-flow (RPF), filtration fraction (FF), urinary albumin and/32-microglobulin-excretion rates. Glucagon infusion resulted in a fourfold increase in plasma glucagon concentration. The infusion induced a significant increase in GFR (+9%), FF (+ 9%) and urinary fl2-microglobulin exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
3

Year Published

1983
1983
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 10 publications
3
38
3
Order By: Relevance
“…This evidence may suggest that glucagon can haemodynamically in¯uence both selective (low molecular weight) and non selective (high molecular weight) proteinuria, potentially increasing the risk to develop focal of diffuse glomerulosclerosis and kidney disease in central obesity. 39,40 In agreement with previous studies, 14,42 the increase of urinary excretion of a1 microglobulin, found in patients with CO, suggests that glucagon can negatively in¯uence the tubular reabsorption if proteins. Obesity with central body fat distribution might therefore represent a risk to develop proteinuria also with a tubular mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…This evidence may suggest that glucagon can haemodynamically in¯uence both selective (low molecular weight) and non selective (high molecular weight) proteinuria, potentially increasing the risk to develop focal of diffuse glomerulosclerosis and kidney disease in central obesity. 39,40 In agreement with previous studies, 14,42 the increase of urinary excretion of a1 microglobulin, found in patients with CO, suggests that glucagon can negatively in¯uence the tubular reabsorption if proteins. Obesity with central body fat distribution might therefore represent a risk to develop proteinuria also with a tubular mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…We, therefore, have tested IDDM patients under (near) normoglycaemic conditions both at BL and after stimulation (S). A reasonably well-controlled group of patients was chosen in order to alleviate as much as possible the influence of hormones, the levels of which can change during periods of poor metabolic control and influence GFR: growth hormone and growth factors [15], glucagon [16,17], and ketone bodies [18,19],…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of glucagon can produce a rise in glomerular filtration rate (GFR) and renal plasma flow (RPF), although supraphysiological doses have usually been administered (40,41). In addition, a previous study suggested that people with diabetes may have an enhanced glomerular hyperfiltration response to glucagon infusion (40).…”
mentioning
confidence: 99%